2007
DOI: 10.1523/jneurosci.5468-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Visual Phosphene Perception Modulated by Subthreshold Crossmodal Sensory Stimulation

Abstract: Crossmodal sensory interactions serve to integrate behaviorally relevant sensory stimuli. In this study, we investigated the effect of modulating crossmodal interactions between visual and somatosensory stimuli that in isolation do not reach perceptual awareness. When a subthreshold somatosensory stimulus was delivered within close spatiotemporal congruency to the expected site of perception of a phosphene, a subthreshold transcranial magnetic stimulation pulse delivered to the occipital cortex evoked a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 32 publications
5
56
0
2
Order By: Relevance
“…Second, although acoustic startle responses may go along with changes in cortical excitability, they would not be expected to be limited to specific latencies coinciding with visual input given that they would likely generalize to other cortical areas. Third, a previous TMS study of tactile influences on TMS-induced phosphene perception showed that the likelihood of perceiving a visual phosphene (induced by subthreshold TMS) is greatest when the tactile pulse precedes occipital TMS by 60ms (Ramos-Estebanez et al, 2007), matching the peak-latency of increased visual cortex excitability we observed. Notably, their use of subthreshold tactile stimulation, which did not reach perceptual awareness, excluded startle responses as a basis for increased cortical excitability (namely, enhanced phosphene perception).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Second, although acoustic startle responses may go along with changes in cortical excitability, they would not be expected to be limited to specific latencies coinciding with visual input given that they would likely generalize to other cortical areas. Third, a previous TMS study of tactile influences on TMS-induced phosphene perception showed that the likelihood of perceiving a visual phosphene (induced by subthreshold TMS) is greatest when the tactile pulse precedes occipital TMS by 60ms (Ramos-Estebanez et al, 2007), matching the peak-latency of increased visual cortex excitability we observed. Notably, their use of subthreshold tactile stimulation, which did not reach perceptual awareness, excluded startle responses as a basis for increased cortical excitability (namely, enhanced phosphene perception).…”
Section: Discussionsupporting
confidence: 81%
“…We show that occipital TMS has opposing effects on visual and auditory stimulus detection over identical time periods. In a follow-up experiment, we further demonstrate that external auditory stimuli enhance visual cortex excitability as measured by phosphene induction via TMS (Silvanto et al, 2006;Bestmann et al, 2007;Ramos-Estebanez et al, 2007).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In their recent Journal of Neuroscience article, Ramos-Estebanez et al (2007) bridge this gap by taking a novel approach to early visuotactile interactions. The authors asked whether subthreshold sensory stimulation can sum across modalities to produce a reportable percept and, if so, what is the precise timing of the interaction.…”
mentioning
confidence: 99%